Integrating Local Wisdom into Modern Curriculum: Educational Practices from Nusantara and European Contexts - Sami Nabil Ben Ammar (Nusantara Education, 2024)
This study examines how local wisdom can be integrated into modern educational curricula by comparing educational practices in the Nusantara region and several European contexts. The research aims to analyze the strategies used to incorporate cultural values, community knowledge, and traditional practices into contemporary education systems, as well as to identify the implications of such integration for educational transformation in the era of globalization. Methodologically, this study employs a qualitative comparative approach through a systematic review of scholarly literature, policy documents, and selected case studies from both regions. The analysis focuses on curriculum design, pedagogical approaches, and institutional policies that facilitate the inclusion of local cultural knowledge within formal education frameworks. The findings indicate that both regions increasingly recognize the importance of contextualizing education through cultural heritage and local knowledge. In Nusantara, local wisdom is often embedded through community-based learning, character education, and the incorporation of indigenous values such as mutual cooperation, environmental stewardship, and social harmony. Meanwhile, European educational systems tend to integrate local culture through place-based education, heritage studies, and participatory learning models that connect schools with local communities and historical landscapes. Despite differences in institutional structures and policy frameworks, both contexts demonstrate that integrating local wisdom can strengthen students’ cultural identity, promote contextual learning, and enhance the relevance of education in addressing contemporary social challenges. This study contributes to the academic discourse on curriculum transformation by providing a cross-regional perspective on the role of cultural knowledge in modern education systems. It highlights the potential of local wisdom as a pedagogical resource for developing culturally responsive curricula that balance global competencies with local identities. The findings also offer policy-relevant insights for educators and curriculum developers seeking to design education models that are both globally competitive and culturally grounded.